Trust and the household-bank relationship - Miguel Ampudia; Spyros Palligkinis (European Central Bank (ECB), 2018)
We examine the role of trust in households' decisions to hold a bank account and to switch to a new bank. We explore Italian household-level data that contain restricted information on the banks that the households are doing business with, as well as measures of trust in the households' main bank and the banking sector. We find that households who distrust the banking sector are less likely to hold a bank account. Moreover, account holders are more likely to switch to a new main bank if they do not trust their current one. The estimated relationships persist over and above a range of socioeconomic variables.
Keywords: G21; G28; D14; 330; household finance; banking; trust